ACE2, COVID-19 Infection, Inflammation, and Coagulopathy: Missing Pieces in the Puzzle - Abassi, Zaid; Higazi, Abd Al Roof; Kinaneh, Safa; Armaly, Zaher; Skorecki, Karl; Heyman, Samuel N. (Frontiers in Physiology, 2020)
Engulfed by the grave consequences of the COVID19 pandemic, a better understanding of the unique pattern of viral invasion and virulence is of utmost importance. Angiotensin converting enzyme (ACE) 2 is a key component in COVID19 infection. Expressed on cell membranes in target pulmonary and intestinal host cells, ACE2 serves as an anchor for initial viral homing, binding to COVID19 spike-protein domains to enable viral entry into cells and subsequent replication. Viral attachment is facilitated by a multiplicity of membranal and circulating proteases that further uncover attachment loci. Inherent or acquired enhancement of membrane ACE2 expression, likely leads to a higher degree of infection and may explain the predisposition to severe disease among males, diabetics or patients with respiratory or cardiac diseases. Additionally, once attached, viral intracellular translocation and replication leads to depletion of membranal ACE2 through degradation and shedding. ACE2 generates angiotensin (Ang) 1-7, which serves a critical role in counterbalancing the vasoconstrictive, pro-inflammatory and pro-coagulant effects of ACE-induced Ang II. Therefore, Ang1-7 may decline in tissues infected by COVID-19, leading to unopposed deleterious outcomes of Ang II. This likely leads to microcirculatory derangement with endothelial damage, profound inflammation and coagulopathy that characterize the more severe clinical manifestations of COVID-19 infection. Our understanding of COVID-ACE2 associations is incomplete and some conceptual formulations are currently speculative, leading to controversies over issues such as the usage of ACE inhibitors or angiotensin-receptor blockers (ARBs). This highlights the importance of focusing on ACE2 physiology in the evaluation and management of COVID-19 disease.